1994
DOI: 10.1523/jneurosci.14-08-04748.1994
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in aging of the human frontal and temporal lobes

Abstract: This study investigated effects of age and sex on regional brain structure in humans, focusing on the frontal and temporal lobes. Hemispheric volumes were obtained from magnetic resonance images (MRIs) of 96 young (53 men, 43 women; aged 18-40 years) and 34 older (17 men, 17 women; aged 41-80) healthy volunteers. Images (5 mm axial spin-echo, repetition time of 3000 msec and echo times of 30 and 80 msec) were resliced along the anterior commissure-posterior commissure (AC-PC) axis to standardize for difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
188
2
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(214 citation statements)
references
References 70 publications
20
188
2
4
Order By: Relevance
“…Indeed, fMRI research had demonstrated that dichotic listening involves activation not only of temporal areas but also of frontal areas (Jancke & Shah, 2002). Further, it has been found that the frontal lobes in particular are most susceptible to age-related brain changes (Coffey et al, 1992;Cowell et al, 1994). Age-related asymmetry might therefore be stronger in dichotic listening tasks involving increased control of attention processes as is the case in our focussed attention conditions.…”
Section: Increased Asymmetry In Recall Performance In Elderlymentioning
confidence: 63%
“…Indeed, fMRI research had demonstrated that dichotic listening involves activation not only of temporal areas but also of frontal areas (Jancke & Shah, 2002). Further, it has been found that the frontal lobes in particular are most susceptible to age-related brain changes (Coffey et al, 1992;Cowell et al, 1994). Age-related asymmetry might therefore be stronger in dichotic listening tasks involving increased control of attention processes as is the case in our focussed attention conditions.…”
Section: Increased Asymmetry In Recall Performance In Elderlymentioning
confidence: 63%
“…This finding suggests a more rapid loss of normal white matter with aging in men. While it could be speculated that more pronounced atrophy of gray matter structures may have contributed to this finding, this is unlikely (ie, greater loss of gray matter-which has been reported by some to occur in men [30][31][32] -should have left the peak height unaffected rather than caused a decrease because of the increasing relative contribution of the white matter compartment in such a scenario). A recent study using multifrequency MR elastography, which reported a more preserved viscoelasticity of the brain with aging in women than men, is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, this interaction was not expected because most longitudinal studies report either no differences in the age-related decline in cognitive functions for men and women (Aartsen et al, 2004), or, when gender differences are observed, a more pronounced decline for females (Meinz & Salthouse, 1998). However, volumetric imaging studies have shown a stronger effect of aging on the frontal lobes in men than in women (Cowell et al, 1994;Murphy et al, 1996). This finding may explain the age 3 gender interaction found for the SCWT Interference change score.…”
Section: Assessment Of Change 77mentioning
confidence: 99%